Physical Activity Levels in High School Students in West Java during the Covid-19 Pandemic - Beltasar Tarigan; Teten Hidayat (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
The study aimed to obtain empirical evidence about the direct impact of the COVID-19 pandemic on the active lifestyle of high school students in West Java and the activities carried out during the Covid-19 pandemic. The study population included high school students in West Java, while the samples were chosen randomly, involving 1,715 students representing each district in West Java. The research method used was the descriptive quantitative method. The instrument used was a physical activity questionnaire for children (PAQ-C). Data analysis employed Microsoft Excel and SPSS 24. The results showed that the student's active life behavior before the Covid-19 pandemic was mostly distributed in the high (857 people, 50%) and moderate (824 people, 48%) categories. Meanwhile, during the Covid-19 pandemic, the most distribution was in a low category (847 people, 49%). The level of student active behavior before the covid-19 pandemic was in the high category, while the level of student active behavior during the covid-19 pandemic was in a low category. This data showed that the COVID-19 pandemic decreased the student's active living behavior from the moderate to the low category. Before the Covid-19 pandemic, the activities carried out were jogging, traditional sports, football, volleyball, badminton, basketball, futsal, Pencak Silat, strength training, and gymnastics. Meanwhile, the activities carried out during the pandemic included sunbathing, walking, jogging, cycling, watching more TV, playing games, sleeping, sitting around, and helping the elderly.